2017
DOI: 10.1152/ajpcell.00169.2017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms involved in the adaptive regulation of the colonic thiamin pyrophosphate uptake process

Abstract: A considerable amount of the thiamin generated by gut microbiota exists in the form of thiamin pyrophosphate (TPP). We have previously shown that human colonocytes possess an efficient carrier-mediated uptake process for TPP that involves the SLC44A4 system and this uptake process is adaptively regulated by prevailing extracellular TPP level. Little is known about the molecular mechanisms that mediate this adaptive regulation. We addressed this issue using human-derived colonic epithelial NCM460 cells and mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In another study, we examined the effect of infecting NCM460 cells with EHEC (200 MOI; 5 h exposure) on level of TPPT protein expression. This was done by means of western blotting using specific polyclonal antibodies against the TPP transporter [25]. The result showed a significant (P < 0.01) reduction in the level of expression of the TPPT protein in cells infected with EHEC compared to uninfected controls (Fig 1D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, we examined the effect of infecting NCM460 cells with EHEC (200 MOI; 5 h exposure) on level of TPPT protein expression. This was done by means of western blotting using specific polyclonal antibodies against the TPP transporter [25]. The result showed a significant (P < 0.01) reduction in the level of expression of the TPPT protein in cells infected with EHEC compared to uninfected controls (Fig 1D).…”
Section: Resultsmentioning
confidence: 99%
“…We also shown that this uptake system is specific for TPP and does not transport the free form of vitamin B1, i. e., free thiamin. In addition, we have characterized different cell biology and regulatory aspects of this colonic TPPT system [20, 24, 25]. Currently, there is little known about the effect of external/ environmental factors on the function of this newly identified uptake system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were euthanized, the colonic tissue was removed and prepared colonic crypts as described before [4143]. The generated colonoids were treated with 1mM NaB for 24 hrs and used for mRFVT3 protein, mRNA and hnRNA expression studies.…”
Section: Methodsmentioning
confidence: 99%
“…For ex vivo studies, we used 8–10-weeks old male C57BL/6 mice (Jackson Laboratory, Bar Harbor, ME) to generate colonoids as described before [4143]. Mice were euthanized, the colonic tissue was removed and prepared colonic crypts as described before [4143]. The generated colonoids were treated with 1mM NaB for 24 hrs and used for mRFVT3 protein, mRNA and hnRNA expression studies.…”
Section: Methodsmentioning
confidence: 99%